Pengantar Dasar Kalkulus: Turunan dan Integral - Puspitasari, Sarmila (Cahaya Ilmu Bangsa Institute, 2025)
This article briefly introduces the basic standards in calculus idea, with a unique focus on derivatives and integrals. This look at targets to assist readers understand the fundamentals of calculus and its packages in numerous fields of science and enhance readers' capacity to investigate and solve calculus-associated issues. The information is secondary facts from books and journals posted nationally and across the world. statistics series techniques on this examine have been performed via listening, noting, and attractive techniques. statistics validation techniques use triangulation strategies, researchers increase and combine principles and ideas contained in articles, journals, and books as one kind of information validation. The consequences of calculus studies study feature and have modified within the form of differential (by-product) and essential. There are two sorts of integrals 1) indispensable actually, 2) vital indefinitely. This research concludes that derivative and critical are primary concepts in calculus used to discover modifications in capabilities in an c program languageperiod and have the same price as the region under the characteristic curve.